Penurunan Change Over Time Automatic Machine Filling di PT XYZ Menggunakan Metode SMED - Suhendra, Suhendra; Putra, Fibi Eko; Juliantoro, Krisna B.; Fitra, Adi (JURNAL TEKNIK INDUSTRI, 2022)
PT. XYZ is a company engaged in the manufacturing of paints, both water based and solvent based. Every year the growth of paint sales is 11-13%. The company's ability to meet demand based on consumer needs adjustments causes many product variants to be made, thus affecting the change over time for each product change. The purpose of this research is to reduce the change over time from base A (white) products to base C products (transparent) using the Single Minute Exchange of Dies (SMED) method. This method can identify the activities carried out in the product change over process to be separated into two activities, namely internal activities, and external activities. Before the repair, the change over time required by the company was 63 minutes of the company's target of 30 minutes, after applying the SMED method, the change over time was 33 minutes. PT. XYZ saves 30 minutes, by turning internal activities into external activities. Save 50% time. Keywords: Change Over Time, Internal Activities, External Activities, SMED